Pengembangan Model Latihan Teknik Service Atas Bola Voli untuk Mahasiswa Pendidikan Jasmani Universitas Muhammadiyah Sorong - Kurniadi, Agus; Istiyono; Bakar, Abu; Robi, La; Mawardi; Emayanti (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This research develops a service technique learning module for volleyball for Physical Education students of the University of Muhammadiyah Sorong with the ADDIE R&D model. Two groups were involved: experiment (using modules) and control (conventional methods). The average pre-test of the experimental group was 60 and the control group was 58. After treatment, the experimental group's post-test score rose to 85, the control was only 70. A 42% increase in the experimental group demonstrated the effectiveness of the module. The t-test yielded p = 0.000 (experiment) and p = 0.003 (control), showing a significant difference. More than 85% of students stated that the modules were easy to understand and helpful with practice, proving that they were effective in use.